Roland S. Morris papers - Morris, Roland S. (Roland Sletor), 1874-1945.
Correspondence, memoranda, speeches, reports, newspaper clippings, photographs, and other papers relating primarily to Morris's service as U.S. ambassador to Japan (1917-1921) and to his special missions to Siberia (1918-1919). Subjects include the Allied intervention in Siberia, 1918-1920. Includes typewritten copies of a translation of a diary of a Japanese mission to the U.S. (1860) and official telegrams exchanged with U.S. Secretary of State Robert Lansing. Also includes papers pertaining to Morris's work at the University of Pennsylvania. Correspondents include William Jennings Bryan, Robert Lansing, Breckinridge Long, Vance McCormick, L.S. Rowe, and Woodrow Wilson.
Lawyer, diplomat, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bryan, William Jennings, -- 1860-1925 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Long, Breckinridge, -- 1881-1958 -- Correspondence; McCormick, Vance Criswell, -- 1872-1946 -- Correspondence; Rowe, L. S. -- 1871-1946 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; University of Pennsylvania; International law; Universities and colleges -- Pennsylvania; Japan -- Foreign relations -- United States; Siberia (Russia) -- History -- Revolution, 1917-1921.; Soviet Union -- Foreign relations -- United States; Soviet Union -- History -- Allied intervention, 1918-1920.; Diplomatic and consular service, American -- Japan; Diplomatic and consular service, American -- Soviet Union; United States -- Foreign relations -- Japan; United States -- Foreign relations -- Soviet Union; Diplomats; Educators; Lawyers